EFFECTS OF NET PROFIT MARGIN, CURRENT RATIO AND DIVIDEND PAYOUT RATIO ON PRICE EARNING RATIO AND PRICE BOOK VALUE (A Study on Consumer Goods Companies Listed in Indonesia Stock Exchange for the Period (2011-2013) - Aisyah, Siti; Rodoni, Ahmad (Aktualita Manajemen, 2016)
AbstractInvesting in stocks is a high risk investment, in which investors can gain big profit and vice versa can suffer losses not small. Therefore, investors are required to be cautious in decision-making. This study aimed to analyze the effects of Net Profit Margin, Current Ratio and Dividend Payout Ratio, on Price Earning Ratio and Price Book Value. It was investigated which independent variables having the most dominant effects on consumer goods companies listed in Indonesia Stock Exchange for the period 2011-2013. The samples used in this study were 16 companies listed in the Indonesia Stock Exchange and the Indonesian Capital Market Directory (ICMD) for the period 2011-2013. This research used purposive sampling. The analytical method used in this study was multiple linear regression analysis. From the test result of independent variables on price earning ratio, it is found that current ratio and net profit margin have no significant negative effect, meaning that the hypothesis is rejected, while dividend payout ratio has significant effect on price earning ratio, meaning that the hypothesis is accepted. From the test results of independent variables on price book value, it is found that net profit margin and dividend payout ratio have significant positive effect on price book value, meaning that the hypothesis is accepted, while current ratio has no significant effect, meaning that the hypothesis is rejected. From the test results of variables collectively from the first model and the second model, it is found that net profit margin, current ratio, and dividend payout ratio have significant positive effect on price earning ratio and price book value. The most dominant variable is net profit margin that has effect on price book value. Â Keywords: Net Profit Margin, Current Ratio, Dividend Payout Ratio, Price Earning Ratio and Price Book Value